2021
DOI: 10.1111/myc.13266
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia indicates poor outcome in patients with infected pancreatic necrosis

Abstract: Background Intra‐abdominal fungal infection (AFI) and candidemia are common in patients with acute pancreatitis (AP), but with limited and conflicting reports on their clinical impacts. This study aims to evaluate the clinical impacts of AFI and candidemia in infected pancreatic necrosis (IPN). Methods A single‐centre, prospective cohort including 235 consecutive patients with IPN between January 2010 and September 2020 was analysed to study the clinical impacts of AFI and candidemia. Results Of the 235 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The vast majority of CAP patients received antibiotics before the IPN intervention because of suspected infections with possible manifestations. In line with previous studies, our cohort demonstrated that antibiotic therapy before intervention did not significantly impact the outcomes, which may also increase the risk of drug resistance and incidence of fungal infections [ 5 , 32 ]. Given the size and limitations of these retrospective data, the comparison between monotherapy and combination prophylactic antibiotic therapy remains to be studied.…”
Section: Discussionsupporting
confidence: 89%
“…The vast majority of CAP patients received antibiotics before the IPN intervention because of suspected infections with possible manifestations. In line with previous studies, our cohort demonstrated that antibiotic therapy before intervention did not significantly impact the outcomes, which may also increase the risk of drug resistance and incidence of fungal infections [ 5 , 32 ]. Given the size and limitations of these retrospective data, the comparison between monotherapy and combination prophylactic antibiotic therapy remains to be studied.…”
Section: Discussionsupporting
confidence: 89%
“…An infectious complication of AP cannot be arbitrarily defined as IPN, and it also needs to include bacteraemia or pulmonary infection ( Wu et al., 2022a ). Moreover, whilst it is often overlooked, bacteraemia, especially MDR-GNB bacteraemia, may pose a serious threat to IPN patients ( Ning et al., 2021a ). MDR-GNB bacteraemia mortalities have been reported in several studies of hospital- onset infections, but they still have not been fully addressed in IPN patients ( Tsai et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%